Reservoir quality of tight oil plays in lacustrine rift basins: Insights from early Cretaceous fine-grained hydrothermal dolomites of the Erlian Basin, NE China. (February 2021) - Yang, Zhe; Zhong, Dakang; Whitaker, Fiona; Sun, Haitao; Su, Chen; Cao, Xuan
Abstract: There has been increasing recognition of fine-grained dolomitic sediments in continental rift basins, but research has tended to focus on their petrography, geochemistry and genesis, rather than the pore characteristics that determine tight oil and gas reservoir quality. This paper presents a classification of pore types for dolomitic sediments influenced by hydrothermal processes from the early Cretaceous Erlian Basin, and examines relations between pore types to infer underlying genetic processes and controls as a precursor to predicting their distribution. We recognize three pore types: (1) primary porosity, which includes inter-crystalline pores between hydrothermal minerals within granules and nano-scale pores within fine matrix; (2) secondary dissolutional porosity, including inter-crystalline dissolved pores in granules, mouldic pores in laminae and bandings and selectively dissolved pores in argillaceous matrix, as well as large vugs in breccias; and (3) fracture porosity, including low-angle dissolved fractures, bedding-parallel microfractures and high-angle tectonic fractures. Both hydrothermal and hydrocarbon-related fluids caused significant dissolution, generating secondary pores that form the largest volume of reservoir storage. Channeling of aggressive fluids via low-angle fractures localized dissolution in the matrix and significantly enhanced permeability. Vertical fractures have a lesser impact on porosity but contribute to improved pore network connectivity. These relationships reflect dolomite accumulation within a tectonically-active extensional setting, with associated fault and fracture networks providing conduits for hydrothermal fluids. These fluids are responsible for formation of the dolomitic reservoir rocks and their diagenesis and may result in a characteristic suite of pore types. The high heat flux ensured rapid maturation of source rocks and may have played an important role in generating additional dissolutional porosity. Given the tight nature of reservoirs in such lacustrine systems, a systematic understanding of the nature and evolution of the pore network is key to identifying productive "sweet spots" in the vicinity of faults for de-risking future hydrocarbon exploration and also in developing such settings for geothermal energy. Highlights: Lacustrine fine-grained hydrothermal dolomites form sweet spots in tight oil reservoirs. Dolomites and associated hydrothermal minerals host inter-crystalline porosity. Corrosion by hydrothermal and hydrocarbon-related fluids forms secondary pores. Fractures control development of diagenetic porosity and core-plug permeability.